Overview of salivary pH in seniors with hypertension in work area of BLUD UPTD Puskesmas Banjar 2: Gambaran pH saliva pada manula penderita hipertensi di wilayah kerja BLUD UPTD Puskesmas Banjar 2 - Siagian, Eklesia R.; Nisa, Khoirun; Medina, Wina Zahra; Calosa, Beby Tara; Hakim, Miranti; Setiawan, Ignatius (Makassar Dental Journal PDGI Makassar, 2025)
Hypertension can have an impact on oral conditions, including a decrease in salivary pH and viscosity which has the potential to affect tooth structure due to enamel demineralisation. The study describes the description of hypertension conditions on salivary pH in seniors in the BLUD UPTD Puskesmas Banjar 2 work area in October 2024. Descriptive study was conducted on subjects who were willing and met the inclusion criteria; measured blood pressure and salivary pH using litmus paper on 60 respon-dents aged 54-80 years with a history of hypertension with blood pressure ≥140/90 mmHg. Respondent data were 63% aged 61-70 years and 90% were female. Most respondents (90%) had mild hypertension with the highest pH of 5 and 6. Salivary acidi-ty tends to decrease as the severity of hypertension increases. It was concluded that hypertension in the elderly not only risks systemic health but also has a significant impact on oral health. The decrease in salivary pH due to hypertension needs to be a concern in the oral health care of the elderly, especially to prevent complications due to a more acidic oral environment.